Management of Tanah Laba Pura as a Supporting Facility for Tourism in Ubud Village - Dewi, Ida Ayu Made Wahyuni; Suwitra, I Made; Renaya, Nengah (RIRAI Publisher, 2024)
ABSTRACT This paper aims to find an ideal concept in managing Tanah laba pura to support tourism and provide benefits for the temple itself and for tourism. The problems discussed are how the conversion of Tanah laba pura is used as a means of supporting tourism and how the legal protection of Tanah laba pura is used as a means of supporting tourism in Ubud Village. The type of research used is empirical legal research, with a statute approach, a conceptual approach, and a sociological legal approach. The sources of research data are primary and secondary data sources. Furthermore, it is analyzed using sociological or teleological interpretation analysis techniques. The results of the study show that the benefits of converting Tanah laba pura in Ubud Village are to repair and maintain the temple building, to cover all religious ceremonial activities of the temple such as piodalan, to help the krama desa in the cost of repairing and maintaining the temple building, and to support tourism facilities in improving the quality of tourism in Ubud. Legal protection of temple land used as a means of supporting tourism in Ubud Village is regulated in the Decree of the Minister of Home Affairs No. SK.556/DJA/1986, where temples are declared as state legal entities that can own land with ownership rights